Reception of Danielius Kleinas’s Ideas in Povilas Frydrichas Ruigys’s Grammar Anfangsgründe einer Littauischen Grammatick (1747) - Aleknavičienė, Ona (Senoji Lietuvos literatūra, 2024)
The article analyses the reception of Danielius Kleinas’s ideas in Povilas Frydrichas Ruigys’s grammar Anfangsgründe einer Littauischen Grammatick (1747, hereinafter RG). Two aims were pursued: (1) to single out Kleinas’s ideas that Ruigys found relevant and suitable for describing the language of the mid-eighteenth century and (2) to identify the intentions of Ruigys in adopting them.Using an analytical interpretive approach based on philological analysis, it is shown that Kleinas’s Grammatica Litvanica (1653, hereinafter KG) was a particularly important source. The need of the Age of Enlightenment to learn about the world and to educate society is highlighted in discussing the motives for adopting and adapting ideas. The study of the reception of Kleinas’s ideas leads to the following conclusions:1. Frequent references to KG, both explicit and implicit, point to a similar school of linguistic thought and the acceptability of its ideas.2. KG was a particularly important source in two respects: (1) selecting a dialect for grammar and distinguishing it from others and (2) developing an extensive section on syntax.3. By adopting Kleinas’s key idea of choosing one dialect as the basis for the description of the Lithuanian language, Ruigys expanded its area to two counties: Įsrutis (Ger. Insterburg) and Ragainė (Ger. Ragnit). He considered the other dialects in Prussia and Lithuania Major as secondary. Ruigys was the first to classify Lithuanian dialects by the opposition main : secondary or centre : periphery.4. By placing emphasis on the stability, universality, and prestige of the main dialect in relation to other dialects, Ruigys continued the tradition of forming standard language on the basis of one dialect, which was initiated by Kleinas. In the eighteenth century, this was relevant for the written form of the language.5. By introducing secondary dialects, he aimed to facilitate the integration of individuals appointed to priesthood in a new linguistic environment. This was important for the spoken form of the language.6. In preparing a grammar for learning Lithuanian by non-Lithuanians, Ruigys paid considerable attention to syntax. By adopting Kleinas’s ideas and expanding them, he sought to develop the ability to produce a coherent text. The ability to generate well-formed sentences is important for both written and spoken language.7. One of the characteristics of the language teaching methodology developed by Ruigys was the development of linguistic communicative competence. In the Age of Enlightenment, this was particularly necessary for the organisation of public education through churches and schools. Taking up earlier ideas and adapting them to the needs of the eighteenth century, Ruigys developed a tool for non-Lithuanians to learn Lithuanian, to develop linguistic competence appropriate to their duties, and to adapt to a new environment.8. RG is focused not only on setting out the basics of the language but also on reducing the distance between written and spoken language.9. Since the description of the grammatical structure of the Lithuanian language in the mid-seventeenth century was suitable as a basis for a grammar of the mid-eighteenth century, it evidences the slight change in the language itself.
Keywords: Danielius Kleinas; Povilas Frydrichas Ruigys; grammar of the Lithuanian language; inguistics of seventeenth-eighteenth-century Prussian Lithuania